The biology of Canadian weeds. 139. Rhamnus cathartica L. - Qaderi, Mirwais M; Clements, David R; Cavers, Paul B (Canadian Journal of Plant Science, 2009)
European buckthorn, Rhamnus cathartica L., is an introduced shrub or small tree of forests, thickets, open pastures, hedgerows, roadsides, and riparian habitats. In Canada, it is found from Alberta east to the Maritimes, but is absent from Newfoundland. It is particularly abundant in southern Ontario. Problems arise from its status as an alternate host for the fungi Puccinia coronata Corda. f. sp. avenae Eriks., which causes crown rust and leaf rust of oats and for Puccinia coronata var. hordei Jin & Steff., which causes crown rust of barley. It is also the overwintering host for the recently invasive soybean aphid, Aphis glycines Matsumura, which has been described as a serious threat to soybean production in North America. Prolific fruit production, in combination with extensive seedling establishment and shade tolerance, allows R. cathartica to dominate an understorey quickly. Its ability to tolerate a wide range of conditions, at least in fairly moist areas, may lead to further expansion of its Canadian range. Control strategies should focus on reducing populations in close proximity to oats, soybeans or barley and to reduce its abundance in areas of ecological importance. Key words: Rhamnus cathartica, European buckthorn, Puccinia coronata, soybean aphid, weed biology